Theoretical and experimental evidence of conformational transformation in stereoisomers of nucleoside analogues. Issue 20 (2nd September 2018) - Hernández‐Hernández, Luis Alberto; Yi, Ruiqin; Cleaves, Henderson James; Fuentes‐Cabrera, Miguel; Sumpter, Bobby G.; Hernández‐Hernández, Arturo; Rangel, Eduardo; Vallejo, Emmanuel
Abstract: A theoretical and experimental characterization of N(1)‐(2′, 3′‐dihydroxypropil)thymine (DHPT), a potential prebiotic nucleoside analogue of 5‐methyluridine, is performed. A proposed methodology based on a solvation method was used to study conformational transformations of the different low‐energy conformers of DHPT according to time‐dependent IR spectroscopy. NMR and CD spectroscopy provides additional evidence of these transformations. The conformational transformations appear to be due to solvent and DHPT interactions. This highlights the importance of experimental conditions on conformer ratio equilibrium, in particular, the interpretation of experimental conditions used for determining the stereoisomers' absolute configuration. Abstract : Nucleoside analogues are molecules that differ from the canonical ones in that they are comprised of a noncanonical DNA base, sugar, or both. Interactions between nucleoside analogues and solvent molecules are proposed as the main responsible for their conformational transformations, which were studied both experimentally and computationally. The evidence of these transformations is provided by time‐dependent infrared spectra and made apparent by the variation of intensity related to a specific stereoisomer.